2016
DOI: 10.2217/bmm-2016-0209
|View full text |Cite
|
Sign up to set email alerts
|

Potential Usefulness of Apolipoprotein A2 Isoforms for Screening and Risk Stratification of Pancreatic Cancer

Abstract: Given the low incidence of pancreatic cancer in the general population, screening of pancreatic cancer in the general population using invasive modalities is not feasible. Combination of invasive screening with noninvasive biomarkers for pancreatic cancer and its precancerous lesions has the potential to reduce mortality due to pancreatic cancer. In this review, we focus on biomarkers found in the blood that can indicate early-stage pancreatic cancer, and we discuss current strategies for screening for pancrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 63 publications
0
40
0
Order By: Relevance
“…Recently, we identified unique processing patterns of c‐terminal amino acids of apolipoprotein A2 (ApoA2) in patients with pancreatic cancer . In the bloodstream ApoA2 can be found in 5 dimeric isoforms (ApoA2i) . In healthy subjects, 3 basic isoforms are found which we labeled ApoA2‐ATQ/ATQ, ApoA2‐ATQ/AT and ApoA2‐AT/AT), by the lengths of each of the homomers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we identified unique processing patterns of c‐terminal amino acids of apolipoprotein A2 (ApoA2) in patients with pancreatic cancer . In the bloodstream ApoA2 can be found in 5 dimeric isoforms (ApoA2i) . In healthy subjects, 3 basic isoforms are found which we labeled ApoA2‐ATQ/ATQ, ApoA2‐ATQ/AT and ApoA2‐AT/AT), by the lengths of each of the homomers.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] In the bloodstream ApoA2 can be found in 5 dimeric isoforms (ApoA2i). [10][11][12][13] In healthy subjects, 3 basic isoforms are found which we labeled ApoA2-ATQ/ ATQ, ApoA2-ATQ/AT and ApoA2-AT/AT), by the lengths of each of the homomers. Patients with PDAC show additional isomers formed through two aberrant processing patterns of ApoA2i: a hyper-processing pattern of ApoA2i, which leads to predominantly light isoforms such as ApoA2-AT/AT, ApoA2-AT/A and ApoA2-A/A, and a hypo-processing pattern which leads to a predominance of heavy isoforms such as ApoA2-ATQ/ATQ.…”
Section: Introductionmentioning
confidence: 99%
“…AII is the second richest protein in HDL and is mainly synthesized in liver. The 9 kDa mass belongs to pro‐Apo‐AII (P02652); 17 kDa is a glycosylated, polypeptide chain of Apo‐AII, the alteration in this isoform being identified in pancreatic cancer and its precancerous lesions (Honda & Srivastava, ). The presence of the SAA family is confirmed by the 12 kDa (nonglycosylated) peak.…”
Section: Resultsmentioning
confidence: 99%
“…Honda (27) A significant reduction in apoA2-ATQ/AT was confirmed in the plasma/serum of any stage of PDAC.…”
Section: Blood-based Biomarkers For Early Detection Of Pdacmentioning
confidence: 85%
“…Such findings suggest apoA2 isoforms as potential biomarkers for filtering the general population for individuals at higher risk of PDAC. Although the mechanisms underlying these findings are still unknown, we have previously reported that specific abnormal processing patterns of amino acid in the C-terminal ends of apoA2 homodimer were observed in PDAC or autoimmune pancreatitis (AIP) [27,28]. Hayasaki et al recently reported that apoA2-ATQ levels seem to reflect pancreatic atrophy and insufficient secretion of circulating pancreatic enzymes, and could provide a biomarker to assess pancreatic exocrine disorder [29].…”
Section: Blood-based Biomarkers For Early Detection Of Pdacmentioning
confidence: 99%